The Failed Treatment of MDR-TB in Three Generations: A Case Study of the Household in Northeastern, Thailand - Srithongtham, Orathai; Thabuddha, Ubonsri; Sangawong, Supasai (Open Science Journal, 2018)
Introduction: In Thailand TB and MDR-TB treatment was found in all levels of the unit of health service system, but the failed treatment especially for MDRTB was found 8.2% in the lower part of northeastern Thailand. In the complex situation, only the medical care cannot eradicate MDR-TB. This study aimed to explain the failure treatment of patient with MDR-TB over 3 generations within 1household. Method: This qualitative method collected data by in-depth in the province located at northeast Thailand; 5 patients and failure treatment of MDR-TB were investigated. The data was analyzed using content analysis. Introduction: In Thailand TB and MDR-TB treatment was found in all levels of the unit of health service system, but the failed treatment especially for MDRTB was found 8.2% in the lower part of northeastern Thailand. In the complex situation, only the medical care cannot eradicate MDR-TB. This study aimed to explain the failure treatment of patient with MDR-TB over 3 generations within 1household. Method: This qualitative method collected data by in-depth in the province located at northeast Thailand; 5 patients and failure treatment of MDR-TB were investigated. The data was analyzed using content analysis. Result: One grandmother, 78 years old, have had twice received treatments and still alive. The mother failed treatment and died from MDR-TB at 54 years old aggravated by noncompliance to drug treatment. The father defaulted treatment due to alcohol consumption, and the second treatment was cured but the subject died at 61 years old. The son and daughter comprised default treatment caused from the household problem of low income, drug addiction, alcohol consumption and divorce. The elder brother did not return to treatment and his symptoms worsened. However, the younger sister, 21 years old, returned to treatment for 4 months. The supportive factors of failed treatment that led patients to cease taking drugs more than 2 months and deny continuing treatment included low income, household problems and drug addiction. Recommendation: Only the medication could not cure or achieve successful treatment, but socio-economic factors such as the understanding of the patient’s context was crucial equally the same as the MDR-TB drug. This factor was effecting to compliance of MDR-TB patient care and treatment.